IIT Varanasi at HASOC 2019 : Hate speech and offensive content identification in indo-european languages - Mishra A.; Pal S. (My University, 2025)
The track aims to develop a system that identifies hate speech and offensive content in the document and further classifies them into hate speech, offensive content, or usage of profane words. Also, it deter- mines whether hate speech is targetted to some individual or a group. We use bidirectional long short term memory along with attention across all languages (English, German, and Hindi) in the track. © Copyright 2019 for this paper by its authors.